Early versus Delayed Endoscopic Sinus Surgery in Patients with Chronic Rhinosinusitis: Impact on Health Care Utilization. (8th January 2015) - Benninger, Michael S.; Sindwani, Raj; Holy, Chantal E.; Hopkins, Claire
Abstract : Objective: To evaluate the impact of early versus delayed endoscopic sinus surgery (ESS) in terms of postoperative health care utilization, using a patient cohort with chronic rhinosinusitis (CRS). Study Design: Retrospective administrative database analysis. Setting: US‐based primary and secondary sites of care. Subjects and Methods: CRS patients with ESS in 2010—with no other ESS before 2010 and with complete medical history from 2004 to 2012—were identified within the MarketScan database. Patients were characterized by time interval of first sinusitis or nasal polyposis diagnosis to ESS and grouped as following: group 1, < 1 year (n = 818); group 2, 1 to <2 years (n = 247); group 3, 2 to <3 years (n = 274); group 4, 3 to <4 years (n = 364); group 5, 4 to <5 years (n = 595); and group 6, ≥5 years (n = 535). Outpatient visits/procedures and prescriptions associated with sinusitis and/or nasal polyps were analyzed for 1 year preoperatively and 2 years postoperatively. Subanalyses were conducted on separate cohorts with or without asthma or polyps, within each group. Results: Patients in group 1 had significantly fewer visits and prescriptions than patients in group 6 (postoperative visits: group 1, 4.45 [95% CI, 4.06‐4.84]; group 6, 6.70 [95% CI, 6.10‐7.30; prescriptions: group 1, 4.54 [95% CI, 4.12‐4.96]; group 6, 7.61 [95% CI, 6.92‐8.31]). Gradual increases in utilization were observed from groups 1 to 6. Subanalysis of patients with and without asthma or polyps showed similar findings. Conclusion: Early intervention after diagnoses of CRS, with or without asthma or polyps, is associated with lower health care utilization than intervention after many years of medical management.